Porous nanofiber lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
A method combining PAN, PVP, and SAN with lithium-rich manganese-based materials under controlled atmospheres forms a porous nanofiber structure, addressing the complex electrospinning process and improving cycle stability and rate performance.
Patent Information
- Application Number
- CN202411380967.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-17
AI Technical Summary
Existing lithium-rich manganese-based positive electrode materials face issues such as a complex electrospinning process, poor combination with high molecular polymers, leading to low rate performance and poor cycle stability due to first-circle lattice oxygen escape and side reactions.
A method involving mixing high molecular polymers like PAN, PVP, and SAN with a lithium-rich manganese-based precursor and lithium salt, followed by spinning and sintering under controlled nitrogen and oxygen atmospheres, forming a porous nanofiber structure with carbon doping and coating, achieving a hierarchical porous structure.
The method results in a porous nanofiber lithium-rich manganese-based positive electrode material with high discharge specific capacity, high initial efficiency, good cycle performance, and rate retention, by enabling gradual contact with the electrolyte and reducing side reactions.
Smart Images

Figure BDA0005069895240000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of positive electrode materials, and in particular relates to a porous nanofiber lithium-manganese-rich positive electrode material and a preparation method and application thereof. Background Art
[0002] In the field of lithium-ion batteries, lithium-rich manganese-based positive electrode materials have the advantages of high theoretical specific capacity, wide charge and discharge range, and low price, and have received widespread attention and attention from technicians. However, when lithium-rich manganese-based positive electrode materials work under high voltage, there is a problem of first-circle lattice oxygen escape, resulting in low first-circle coulombic efficiency, frequent side reactions, fast voltage decay, poor rate performance and poor cycle stability.
[0003] In the prior art, nanofibers are prepared by electrospinning, which is a simple and easy-to-control process. The prepared nanofibers can be used as carbon-based materials to carry lithium, and have the advantages of high specific surface area and inorganic loading. However, there are also problems such as the complex process of preparing hierarchical porous structures; and there is no combination of high molecular polymers and lithium-rich manganese-based positive electrode materials to improve the performance of the positive electrode materials. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects in the prior art such as the complicated electrospinning process, the inability to effectively combine the polymer and the lithium-rich manganese-based positive electrode material, resulting in low rate performance and poor cycle stability of the prepared positive electrode material, thereby providing a porous nanofiber lithium-rich manganese-based positive electrode material and its preparation method and application.
[0005] To this end, the present invention provides the following technical solutions.
[0006] The present invention provides a method for preparing a porous nanofiber lithium-rich manganese-based positive electrode material, comprising the following steps:
[0007] (1) mixing a high molecular polymer, a lithium-rich manganese-based precursor and a lithium salt to prepare a spinning solution;
[0008] (2) Spinning and sintering;
[0009] The high molecular polymer includes PAN, PVP and SAN;
[0010] The sintering atmosphere includes nitrogen and oxygen, and the volume ratio of the nitrogen to the oxygen is (5.5-13):1.
[0011] In an optional embodiment, the step (1), the specific steps of mixing include: dissolving the high molecular polymer in a solvent, stirring for the first time, adding a lithium-rich manganese-based precursor and a lithium salt, and stirring for the second time;
[0012] Preferably, the first stirring time is 2-6h;
[0013] Preferably, the second stirring time is 10-16h;
[0014] It is understood that the solvent used is a common solvent in the art, including N,N-dimethylformamide;
[0015] In an optional embodiment, the mass ratio of PAN, PVP and SAN is (1.5-2.5):1:(0.5-1.5);
[0016] Preferably, the mass ratio of PAN, PVP and SAN is (1.7-2.3):1:1.
[0017] In an optional embodiment, during the sintering, the sintering atmosphere is introduced in the form of nitrogen and compressed air; the compressed air does not contain moisture and carbon dioxide;
[0018] Preferably, the compressed air comprises nitrogen and oxygen;
[0019] Preferably, the volume ratio of nitrogen to oxygen in the compressed air is (3.5-3.8):1;
[0020] Preferably, the volume ratio of the nitrogen to the compressed air is (0.5-2):1.
[0021] In an optional embodiment, the specific steps of sintering include: heating to 220-300°C at a heating rate of 2-4°C / min, maintaining for 0.5-2h, and then performing heating sintering and cooling sintering;
[0022] Preferably, the temperature-raising sintering includes a first sintering and a second sintering;
[0023] Preferably, the temperature-lowering sintering is performed after the temperature-raising sintering.
[0024] In an optional embodiment, the heating rate of the heating sintering is 2-4°C / min;
[0025] In an optional embodiment, the temperature of the first sintering is 650-750° C., and the time of the first sintering is 6-10 h;
[0026] In an optional embodiment, the temperature of the second sintering is 900-980° C., and the time of the second sintering is 8-12 hours;
[0027] In an optional embodiment, the cooling rate of the cooling sintering is 0.5-1.5°C / min;
[0028] In an optional embodiment, the temperature of the cooling sintering is 550-650° C., and the time of the cooling sintering is 0.5-2 h.
[0029] In an optional embodiment, the lithium-rich manganese-based precursor includes at least one of nickel manganese hydroxide and nickel cobalt manganese hydroxide; preferably nickel manganese hydroxide;
[0030] In an optional embodiment, the lithium salt includes at least one of lithium acetate, lithium hydroxide and lithium carbonate; preferably lithium acetate;
[0031] In an optional embodiment, the mass ratio of the high molecular polymer to the lithium-rich manganese-based precursor is 1:(0.3-0.7);
[0032] In an optional embodiment, the molar ratio of the lithium-rich manganese-based precursor to the lithium salt is 1:(1.3-1.5);
[0033] In an optional embodiment, the molar ratio of nickel element to manganese element in the lithium-rich manganese-based precursor is (35-40): (60-65).
[0034] In an optional embodiment, the spinning process includes electrospinning;
[0035] Preferably, the voltage of the electrospinning is 18-22 kV;
[0036] Preferably, the electrospinning propulsion speed is 0.2-0.8 mL / h.
[0037] Preferably, the receiving distance of the electrospinning is 16-20 cm.
[0038] The invention provides a porous nanofiber lithium-rich manganese-based positive electrode material prepared by the preparation method.
[0039] The present invention provides an application of a porous nanofiber lithium-rich manganese-based positive electrode material prepared by the above preparation method in a lithium-ion battery or a pole piece.
[0040] The technical solution of the present invention has the following advantages:
[0041] 1. The preparation method of the porous nanofiber lithium-rich manganese-based positive electrode material provided by the present invention comprises the following steps: (1) mixing a polymer, a lithium-rich manganese-based precursor and a lithium salt to prepare a spinning solution; (2) spinning and sintering; the polymer comprises PAN, PVP and SAN; the sintering atmosphere comprises nitrogen and oxygen, and the volume ratio of the nitrogen to the oxygen is (5.5-13):1. The porous nanofiber lithium-rich manganese-based positive electrode material prepared by the present invention has high discharge specific capacity, high initial efficiency, good cycle performance and rate retention rate; specifically, the present invention simultaneously adds PAN, PVP and SAN to generate a porous nanofiber lithium-rich manganese-based positive electrode material with carbon doping, carbon coating and hierarchical porous structure in one step, wherein PAN will be carbonized to generate a carbon fiber skeleton, thereby avoiding the collapse of the fiber structure of the porous nanofiber lithium-rich manganese-based positive electrode material; PAN, PVP and SAN will form a hierarchical porous structure with mesopores, micropores, etc. during sintering, thereby realizing the gradual contact between the lithium-rich manganese-based positive electrode material and the electrolyte, thereby improving the cycle performance of the battery. The hierarchical porous structure enables the material to have a high specific surface area, realizes gradual contact and infiltration between the material and the electrolyte, and avoids a large number of side reactions that reduce the cycle performance of the battery and the occurrence of safety problems.
[0042] The present invention can retain the porous carbon structure and partially graphitize, and realize carbon doping and carbon coating at the same time. The volume ratio of nitrogen and oxygen is controlled within the range of (5.5-13): 1, which can improve the initial efficiency, specific capacity and cycle performance of the lithium-rich manganese-based positive electrode material. If it is less than this range, the nitrogen content is too little, and the high molecular polymer is almost completely oxidized, resulting in poor carbon doping and carbon coating effects, low material initial efficiency and poor cycle performance; if it is greater than this range, the nitrogen content is too much, and the layered structure of the lithium-rich manganese-based positive electrode material cannot be formed, and multiple oxygen vacancies appear, resulting in poor material performance, and too little oxygen content easily reduces the high-valent manganese in the material to low-valent manganese, so that the specific capacity of the prepared battery is reduced and the cycle performance is poor.
[0043] 2. The preparation method of the porous nanofiber lithium-rich manganese-based positive electrode material provided by the present invention adopts a unique sintering procedure, and only one sintering process is required to generate a porous nanofiber lithium-rich manganese-based positive electrode material with carbon doping, carbon coating and hierarchical porous structure in one step; specifically, heating to 220-300°C at a heating rate of 2-4°C / min and then maintaining for 0.5-2h is to remove some functional groups of PAN, achieve a higher degree of crosslinking, avoid directly heating to 650-750°C for melting, and retain more carbon for carbon coating and carbon doping;
[0044] In the first sintering, the lithium-rich manganese-based precursor and the lithium source are fully mixed to form a crystalline structure, PAN is partially carbonized to form a preliminary carbon fiber skeleton, PVP and SAN are completely volatilized, and a hierarchical porous structure is formed inside the material; when the temperature is directly raised to 900-980°C, a large amount of lithium source will volatilize, and a stable layered structure cannot be formed, which seriously reduces the performance of the obtained material;
[0045] The second sintering further forms a stable layered structure and crystal grain growth on the formed crystalline phase structure. The second sintering is carried out at 900-980°C to form a suitable primary grain size, which is helpful to improve the specific capacity and cycle performance of the prepared material. PAN retains the porous carbon structure and partial graphitization state while retaining the carbon fiber skeleton, realizing carbon doping and carbon coating; carbon doping can improve the electronic conductivity and rate retention rate of the material, and reduce the irreversible phase change by regulating the structure of the lithium-rich manganese-based positive electrode material, thereby providing the structural stability and cycle performance of the material; carbon coating can not only increase the electronic conductivity and rate retention rate of the material, but also form a protective layer on the surface of the prepared porous nanofiber lithium-rich manganese-based positive electrode material, reduce its side reaction with the electrolyte and the release of lattice oxygen, and improve the cycle performance of the material;
[0046] Sintering by cooling can avoid the thermal stress caused by cooling directly from 900-980℃ to room temperature, which can lead to lattice distortion, reduce the stress within the particles and thus reduce the generation of microcracks inside the material. It can also regulate the grain size to further obtain the ideal primary grain size. DETAILED DESCRIPTION
[0047] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0048] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0049] Example 1
[0050] This embodiment provides a method for preparing a porous nanofiber lithium-rich manganese-based positive electrode material, comprising the following steps:
[0051] (1) Dissolve PAN, PVP and SAN in N,N-dimethylformamide, stir for 3 h, and add Ni 0.35 Mn 0.65(OH)2 and lithium acetate, the second stirring for 12h to obtain a spinning solution; the mass ratio of PAN, PVP and SAN is 2:1:1, and the mass ratio of PAN, PVP and SAN is 2:1:1. 0.35 Mn 0.65 The mass ratio of (OH)2 is 1:0.5; the Ni 0.35 Mn 0.65 The molar ratio of (OH)2 to lithium acetate is 1:1.4; the ratio of the volume of N,N-dimethylformamide to the sum of the masses of PAN, PVP and SAN is 5:1;
[0052] (2) The spinning solution was prepared into a precursor nanofiber membrane by an electrospinning process, wherein the voltage of the electrospinning process was 20 kV, the propulsion speed was 0.5 mL / h, and the receiving distance was 18 cm; the precursor nanofiber membrane was then placed in an atmosphere furnace, the atmosphere of the atmosphere furnace was nitrogen and compressed air in a volume ratio of 1:1 (the volume ratio of nitrogen and oxygen in the compressed air was about 3.65:1), and the temperature program was set to increase the temperature to 260°C at a heating rate of 3°C / min and then keep it warm for 1 hour, then increase the temperature to 700°C at a heating rate of 3°C / min and keep it warm for 8 hours, then increase the temperature to 940°C at a heating rate of 3°C / min and keep it warm for 10 hours, and then cool down to 600°C at a cooling rate of 1°C / min and keep it warm for 1 hour, thereby preparing a porous nanofiber lithium-rich manganese-based positive electrode material.
[0053] Example 2
[0054] This embodiment provides a method for preparing a porous nanofiber lithium-manganese-rich positive electrode material. Compared with Example 1, the only difference is that in step (1), the mass ratio of PAN, PVP and SAN is 1.5:1:1 instead of the mass ratio of PAN, PVP and SAN in Example 1 being 2:1:1.
[0055] Example 3
[0056] This embodiment provides a method for preparing a porous nanofiber lithium-manganese-rich positive electrode material. Compared with Example 1, the only difference is that in step (1), the mass ratio of PAN, PVP and SAN is 2.5:1:1 instead of the mass ratio of PAN, PVP and SAN in Example 1 being 2:1:1.
[0057] Example 4
[0058] This embodiment provides a method for preparing a porous nanofiber lithium-rich manganese-based positive electrode material, comprising the following steps:
[0059] (1) Dissolve PAN, PVP and SAN in N,N-dimethylformamide, stir for 3 h, and add Ni 0.35 Mn 0.65(OH)2 and lithium acetate, the second stirring for 12h to obtain a spinning solution; the mass ratio of PAN, PVP and SAN is 2:1:1, and the mass ratio of PAN, PVP and SAN is 2:1:1. 0.35 Mn 0.65 The mass ratio of (OH)2 is 1:0.35; the Ni 0.35 Mn 0.65 The molar ratio of (OH)2 to lithium acetate is 1:1.4; the ratio of the volume of N,N-dimethylformamide to the sum of the masses of PAN, PVP and SAN is 5:1;
[0060] (2) The spinning solution was prepared into a precursor nanofiber membrane by an electrospinning process, wherein the voltage of the electrospinning process was 20 kV, the propulsion speed was 0.4 mL / h, and the receiving distance was 19 cm; the precursor nanofiber membrane was then placed in an atmosphere furnace, the atmosphere of the atmosphere furnace was nitrogen and compressed air with a volume ratio of 0.8:1 (the volume ratio of nitrogen and oxygen in the compressed air was about 3.65:1), and the temperature program was set to heat up to 290°C at a heating rate of 4°C / min and then keep warm for 1.8 h, then heat up to 670°C at a heating rate of 3°C / min and keep warm for 9 h, then heat up to 910°C at a heating rate of 3°C / min and keep warm for 11 h, and then cool down to 630°C at a cooling rate of 1°C / min and keep warm for 0.6 h, thereby preparing a porous nanofiber lithium-rich manganese-based positive electrode material.
[0061] Example 5
[0062] This embodiment provides a method for preparing a porous nanofiber lithium-rich manganese-based positive electrode material, comprising the following steps:
[0063] (1) Dissolve PAN, PVP and SAN in N,N-dimethylformamide, stir for 3 h, and add Ni 0.35 Mn 0.65 (OH)2 and lithium acetate, the second stirring for 12h to obtain a spinning solution; the mass ratio of PAN, PVP and SAN is 1.7:1:0.7, and the mass ratio of PAN, PVP and SAN is 1.7:1:0.7. 0.35 Mn 0.65 The mass ratio of (OH)2 is 1:0.6; the Ni 0.35 Mn 0.65 The molar ratio of (OH)2 to lithium acetate is 1:1.5; the ratio of the volume of N,N-dimethylformamide to the mass sum of PAN, PVP and SAN is 5:1;
[0064] (2) The spinning solution was prepared into a precursor nanofiber membrane by an electrospinning process, wherein the voltage of the electrospinning process was 19 kV, the propulsion speed was 0.7 mL / h, and the receiving distance was 17 cm; the precursor nanofiber membrane was then placed in an atmosphere furnace, the atmosphere of the atmosphere furnace was nitrogen and compressed air with a volume ratio of 1.8:1 (the volume ratio of nitrogen and oxygen in the compressed air was about 3.65:1), and the temperature program was set to increase the temperature to 240°C at a heating rate of 2°C / min and then keep it warm for 0.7 h, then increase the temperature to 720°C at a heating rate of 3°C / min and keep it warm for 7 h, then increase the temperature to 970°C at a heating rate of 3°C / min and keep it warm for 9 h, and then cool down to 560°C at a cooling rate of 1°C / min and keep it warm for 1.7 h, thereby obtaining a porous nanofiber lithium-rich manganese-based positive electrode material.
[0065] Comparative Example 1
[0066] This comparative example provides a method for preparing a lithium-rich manganese-based positive electrode material. Compared with Example 1, the only difference is that in step (1), PVP and SAN are not added.
[0067] Comparative Example 2
[0068] This comparative example provides a method for preparing a lithium-rich manganese-based positive electrode material, comprising the following steps:
[0069] (1) Ni 0.35 Mn 0.65 (OH)2 and lithium acetate were mixed and stirred for 12h; 0.35 Mn 0.65 The molar ratio of (OH)2 and lithium acetate is 1:1.4;
[0070] (2) In an atmosphere furnace (the atmosphere of the atmosphere furnace is nitrogen and compressed air in a volume ratio of 1:1), the temperature was increased to 260°C at a heating rate of 3°C / min and then kept at this temperature for 1 hour, then the temperature was increased to 700°C at a heating rate of 3°C / min and kept at this temperature for 8 hours, then the temperature was increased to 940°C at a heating rate of 3°C / min and kept at this temperature for 10 hours, and then the temperature was decreased to 600°C at a cooling rate of 1°C / min and kept at this temperature for 1 hour to obtain a lithium-rich manganese-based positive electrode material.
[0071] Comparative Example 3
[0072] This comparative example provides a method for preparing a lithium-rich manganese-based positive electrode material. Compared with Example 1, the only difference is that in step (2), the oxygen atmosphere replaces the nitrogen and compressed air mixed atmosphere of Example 1.
[0073] Comparative Example 4
[0074] This comparative example provides a method for preparing a lithium-rich manganese-based positive electrode material. Compared with Example 1, the only difference is that in step (2), the nitrogen atmosphere replaces the nitrogen and compressed air mixed atmosphere of Example 1.
[0075] Test Case
[0076] The performance tests of the lithium-rich manganese-based positive electrode materials prepared in the above examples and comparative examples are as follows:
[0077] Using N-methylpyrrolidone as a dispersant, lithium-rich manganese-based positive electrode material: carbon black: PVDF (polyvinylidene fluoride) were mixed at a mass ratio of 80:10:10 to prepare a positive electrode slurry, which was evenly coated on a carbon-coated aluminum foil with a coating surface density of 3 cm 2 / mg, and dried in an oven at 80°C for 2h to obtain a positive electrode sheet; in an argon atmosphere in a glove box, a Celgard 2500 separator and a lithium metal sheet were used as the negative electrode sheet, and the electrolyte was 1 mol / L (EC, EMC and DMC in a volume ratio of 1:1:1); a CR2032 button half-cell was assembled in the order of negative electrode sheet, electrolyte, separator, electrolyte and positive electrode sheet.
[0078] The performance of the battery prepared above and the lithium-rich manganese-based composite electrode of the comparative example were tested as follows:
[0079] (1) 0.2C discharge specific capacity test method: At 25°C, the battery is charged at 0.2C and discharged once at 0.2C. The results are shown in Table 1. The first efficiency calculation formula is as follows:
[0080] First effect = 100% × 1 st Discharge specific capacity / 1 st Charge capacity
[0081] (2) Cycle performance test method: At 25°C, the battery was charged at 0.2C, discharged once at 0.2C, and cycled 52 times. The results are shown in Table 1. The cycle performance calculation formula is as follows:
[0082] Cycle performance = 100% × 52 th Discharge specific capacity / 3 rd Discharge specific capacity
[0083] (3) Voltage decay test method: Using the blue-electric test system, after 52 cycles, the average drop in the median discharge voltage per cycle was calculated. The results are shown in Table 1.
[0084] (4) Rate retention test method: At 25°C, the battery was charged at 0.1C, discharged once at 0.1C, and cycled 3 times; the battery was charged at 0.2C, discharged once at 0.2C, and cycled 3 times; the battery was charged at 0.5C, discharged once at 0.5C, and cycled 3 times; the battery was charged once at 0.5C, discharged once at 1C, discharged once at 2C, and discharged once at 5C. The results are shown in Table 1. The rate retention calculation formula is as follows:
[0085] Rate retention rate = 100% × 5C discharge capacity / 0.1C discharge capacity
[0086] Table 1
[0087]
[0088] From Examples 1-5 and Comparative Examples 1-4, the porous nanofiber lithium-rich manganese-based positive electrode material prepared by the present invention has high discharge specific capacity, high first efficiency, good cycle performance and rate retention rate, and the addition of PAN, PVP and SAN can generate a porous nanofiber lithium-rich manganese-based positive electrode material with carbon doping, carbon coating and hierarchical porous structure in one step, with simple steps and convenient operation; sintering under a volume ratio of nitrogen to the oxygen of (5.5-13):1 can form a layered lithium-rich manganese-based positive electrode material structure. From the comparison between Example 1 and Example 2-3, the mass ratio of PAN, PVP and SAN (1.7-2.3): 1:1 is a preferred scheme, and the prepared porous nanofiber lithium-rich manganese-based positive electrode material has high 0.2C discharge specific capacity, first efficiency, cycle performance and rate retention rate, and reduced voltage decay.
[0089] By comparing Example 1 with Comparative Example 1, the 0.2C discharge specific capacity, first efficiency, cycle performance and rate retention rate of Comparative Example 1 without adding PVP and SAN are significantly reduced, and the voltage decay becomes higher. This indicates that the addition of PVP and SAN in the present invention can form a layered porous structure, realize the gradual contact between the lithium-rich manganese-based positive electrode material and the electrolyte, and improve the cycle performance of the battery.
[0090] By comparison between Example 1 and Comparative Example 2, the prepared lithium-rich manganese-based positive electrode material is not as good as the porous nanofiber lithium-rich manganese-based positive electrode material prepared by the preparation method of the present invention in terms of 0.2C discharge specific capacity, first efficiency, cycle performance and rate retention rate, and the voltage decay is reduced.
[0091] By comparison between Example 1 and Comparative Example 3, PAN is completely oxidized under an oxygen atmosphere without nitrogen, and no carbon doping or carbon coating is performed. Its 0.2C discharge specific capacity, first efficiency, cycle performance and rate retention rate are all reduced, and the voltage decay is higher; By comparison between Example 1 and Comparative Example 4, by sintering under a nitrogen atmosphere, the layered structure of the lithium-rich manganese-based positive electrode material cannot be formed, and the high-valent manganese in the lithium-rich manganese-based precursor is reduced to low-valent manganese, and the oxidation is incomplete. The first efficiency of the porous nanofiber lithium-rich manganese-based positive electrode material obtained is reduced, the 0.2C discharge specific capacity, cycle performance and rate retention rate are greatly reduced, and the voltage decay is higher.
[0092] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing a porous nanofiber lithium-rich manganese-based positive electrode material, It is characterized in that The steps include: (1) mixing a high molecular polymer, a lithium-rich manganese-based precursor and a lithium salt to prepare a spinning solution; (2) Spinning and sintering; The high molecular polymer includes PAN, PVP and SAN; The sintering atmosphere includes nitrogen and oxygen, and the volume ratio of the nitrogen to the oxygen is (5.5-13):
1.
2. The preparation method according to claim 1, It is characterized in that The mass ratio of PAN, PVP and SAN is (1.5-2.5):1:(0.5-1.5); Preferably, the mass ratio of PAN, PVP and SAN is (1.7-2.3):1:
1.
3. The preparation method according to claim 1, It is characterized in that During the sintering, a sintering atmosphere is introduced in the form of nitrogen and compressed air; Preferably, the compressed air comprises nitrogen and oxygen; Preferably, the volume ratio of nitrogen to oxygen in the compressed air is (3.5-3.8):1; Preferably, the volume ratio of the nitrogen to the compressed air is (0.5-2):
1.
4. The preparation method according to claim 1, It is characterized in that The specific steps of sintering include: heating to 220-300°C at a heating rate of 2-4°C / min, maintaining for 0.5-2h, and then performing heating sintering and cooling sintering; Preferably, the temperature-raising sintering includes a first sintering and a second sintering; Preferably, the temperature-lowering sintering is performed after the temperature-raising sintering.
5. The preparation method according to claim 4, It is characterized in that The heating rate of the heating sintering is 2-4°C / min; and / or, The temperature of the first sintering is 650-750° C., and the time of the first sintering is 6-10 h; and / or, The temperature of the second sintering is 900-980° C., and the time of the second sintering is 8-12 hours; and / or, The cooling rate of the cooling sintering is 0.5-1.5°C / min; and / or, The temperature of the cooling sintering is 550-650° C., and the time of the cooling sintering is 0.5-2 h.
6. The preparation method according to claim 1, It is characterized in that The lithium-rich manganese-based precursor includes at least one of nickel manganese hydroxide and nickel cobalt manganese hydroxide; and / or, The lithium salt comprises at least one of lithium acetate, lithium hydroxide and lithium carbonate; and / or, The mass ratio of the high molecular polymer to the lithium-rich manganese-based precursor is 1:(0.3-0.7); and / or, The molar ratio of the lithium-rich manganese-based precursor to the lithium salt is 1:(1.3-1.5); and / or, The molar ratio of nickel element to manganese element in the lithium-rich manganese-based precursor is (35-40): (60-65).
7. The preparation method according to claim 1, It is characterized in that The spinning process includes electrostatic spinning.
8. The preparation method according to claim 7, It is characterized in that The voltage of the electrospinning is 18-22 kV; and / or, The electrospinning propulsion speed is 0.2-0.8 mL / h; and / or, The receiving distance of the electrospinning is 16-20 cm.
9. The porous nanofiber lithium-rich manganese-based positive electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the porous nanofiber lithium-rich manganese-based positive electrode material prepared by the preparation method according to any one of claims 1 to 8 in lithium-ion batteries or pole pieces.
